Clustering Districts/Cities In Southeast Sulawesi Province Using Fuzzy C-Means Based On Infectious Disease Cases - Puja Karna, I Kadek Aryandra; Adhi Wibawa, Gusti Ngurah; Ihwal, Muhammad (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This study aims to determine the clustering results and characteristics of districts or cities in Southeast Sulawesi Province based on infectious disease cases in 2022 using the Fuzzy C-Means (FCM) algorithm. The analysis used the standard deviation ratio as a cluster validity measure. The clustering process produced five clusters. Cluster 1 consists of Kendari City which is characterized by a very high number of infectious disease cases. Cluster 2 includes Buton, Konawe, Bombana, North Kolaka and Baubau City which are characterized by low case numbers. Cluster 3 consists of Kolaka and South Konawe both of which have high numbers of cases. Cluster 4 includes Wakatobi, North Buton, North Konawe, East Kolaka, Konawe Islands, West Muna, Central Buton and South Buton which are characterized by very low numbers of cases. Cluster 5 consists of Muna District which is characterized by a moderately high number of infectious disease cases. These results indicate that the FCM method performs well in identifying patterns of disease spread across the region.